Correlation of Gestational Age Assessed by Last Menstrual Period, Antenatal Ultrasonography and New Ballard Score (GAIMS Journal of Medical Sciences, 2025)
Background: Determining gestational age (GA) significantly influences the prognosis of newborns. Of the various methods available for gestational age assessment, gestational age assessment by first trimester ultrasonography (USG) as the most reliable method gestational and by LMP (last menstrual period), is next best surrogate. In remote areas and rural settings in Low and Middle Income Countries, the reliability of LMP based GA assessment is questionable due to low literacy rates and less awareness among women and USG is not cost effective. In such a scenario, GA assessment by clinical methods like New Ballard Score (NBS) seems an attractive alternative. Hence this study was conducted to compare the reliability of GA assessments by LMP and NBS as compared to 1st trimester ultrasonography in our institute.Methods: This was a prospective study carried out at neonatal intensive care unit of a tertiary care teaching hospital of western Gujarat, India, from August 2022 to July 2023. A total of 200 neonates with mother having first trimester scan and who recalls LMP were recruited for the study. Gestational age according to first trimester scan was calculated and compared with gestational age according to LMP and NBS.Results: Gestational age by UGS with NBS show significant correlation (p value